Proposed instructional materials on adjectives geared towards the use of mastery learning strategies for grade five - Elardo, Erlinda Avilla 1940-
The purpose of this study is to develop instructional materials on adjectives for English in Grade V based on the mastery learning strategy which will include the following: descriptive adjectives, word order of adjectives, the -ing form of the verb as an adjective, using proper adjectives, using too/enough with adjectives, and degrees of comparison of adjectives. Moreover, it aimed to provide for the teaching of the components of the language which are phonology, lexicon (vocabulary), and structure, to develop the langauge skills of listening, speaking, reading, and writing, and to provide drills which move from pure manipulation to free communication.